1976
DOI: 10.1007/bf02256359
|View full text |Cite
|
Sign up to set email alerts
|

Tumefactive extramedullary hematopoiesis of the stomach

Abstract: A 3 X 4 cm submucosal gastric mass of extramedullary hematopoeitic tissue occurred in a patient with chronic myelogenous leukemia. Such stomach masses have been misinterpreted as malignant tumor. Tumefactive extramedullary hematopoiesis of the stomach is an infrequent occurrence in patients with extramedullary hematopoiesis but should be considered in the differential diagnosis of patients known to have this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 8 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…As is the case with physiologic EMH in the fetus, the liver and spleen are the usual sites of pathologic EMH. However, nonhepatosplenic EMH (NHS-EMH) has been reported in a myriad of other tissues and organs, including the mediastinum, 1 central nervous system, 2 peripheral nerves, 3 middle ear, 4 pancreas, 5,6 urethra, 7 pharynx, 8 pleura and lungs, 5,9,10 pericardium, 11 heart, 5,12 gastrointestinal tract, 5,13 peritoneum, 5,14 thyroid gland, 15 skin, 5,16 kidney, 5,17,18 adrenal gland, 5 prostate gland, 19 breast, 20 epididymis, 5 and endometrium. 21 Al-though NHS-EMH is often associated with myelofibrosis with myeloid metaplasia (MMM) 17 or thalassemia, 22 it can also accompany other disorders, including hereditary spherocytosis, [23][24][25] sickle cell anemia, 26,27 congenital dyserythropoietic anemia, 28 immune thrombocytopenic purpura, 29 chronic myeloid leukemia, 11,30 polycythemia vera, 31,32 myelodysplastic syndrome, 33 Paget disease, 34 osteopetrosis, 35 and Gaucher disease, 36 and treatm...…”
mentioning
confidence: 99%
“…As is the case with physiologic EMH in the fetus, the liver and spleen are the usual sites of pathologic EMH. However, nonhepatosplenic EMH (NHS-EMH) has been reported in a myriad of other tissues and organs, including the mediastinum, 1 central nervous system, 2 peripheral nerves, 3 middle ear, 4 pancreas, 5,6 urethra, 7 pharynx, 8 pleura and lungs, 5,9,10 pericardium, 11 heart, 5,12 gastrointestinal tract, 5,13 peritoneum, 5,14 thyroid gland, 15 skin, 5,16 kidney, 5,17,18 adrenal gland, 5 prostate gland, 19 breast, 20 epididymis, 5 and endometrium. 21 Al-though NHS-EMH is often associated with myelofibrosis with myeloid metaplasia (MMM) 17 or thalassemia, 22 it can also accompany other disorders, including hereditary spherocytosis, [23][24][25] sickle cell anemia, 26,27 congenital dyserythropoietic anemia, 28 immune thrombocytopenic purpura, 29 chronic myeloid leukemia, 11,30 polycythemia vera, 31,32 myelodysplastic syndrome, 33 Paget disease, 34 osteopetrosis, 35 and Gaucher disease, 36 and treatm...…”
mentioning
confidence: 99%
“…In patients with haematological disorders, this characteristic endoscopic picture should raise a suspicion of extramedullary haematopoiesis in the stomach. To our knowledge, after extensively review, there have been only three reported cases of gastric extramedullary haematopoiesis in the English medical literature 1 2…”
mentioning
confidence: 99%